Job Stress, Role Expectation Conflict, Co-Worker Support, and Work-Life Balance among Muslimah Scholars: A Study in the Indonesian Historical Women Political Movement Members - Siti Mahmudah; Sadari Sadari; Ummah Karimah; Habib Shulton Asnawi (Islamic Guidance and Counseling Journal, 2022)
Women ulama or Muslimah scholars are ordinary people who experience role conflicts, problems with co-worker support, and work-life imbalances which would cause stress in the workplace. Some pieces of literature have examined these issues; however, a study in a specific community like Muslimah scholars who are Indonesian Women's Ulama Conference members (KUPI) is still limited. This study examines the effect of role conflict, co-worker support, and work-life balance on work stress among Indonesian female Ulama. The author uses a quantitative approach with a cross-sectional design. After filling out a consent form, data was collected from Muslimah scholars and members of KUPI. Participants then filled out the questionnaire by self-report. The results showed that most participants had moderate role expectation conflict, co-worker support, work-life balance, and job stress. The variables of role expectation conflict, co-worker support, and work-life balance influence work stress simultaneously. The indirect effect analysis showed only role expectation conflict on job stress through work-life balance, which has a significant effect. This finding indicates that although these women scholars have strategic careers and positions in their workplace, colleagues and family are two crucial things for them.